The Effect of Website Quality (Webqual 4.0) and E-Service Quality on Purchasing Decisions through E-Customer Trust in E-Commerce Shopee - Nasution, Eri Yanti; Kusumah, Ridho (AIBPM Publisher, 2023)
This study intended to identify and analyze website quality (webqual 4.0) and e-service quality on purchasing decisions through e-customer trust in E-Commerce Shopee. This study uses descriptive quantitative methods with accidental sampling techniques and path analysis. Samples in this study were 90 students of the Faculty of Economics and Business, Universitas Muhammadiyah Sumatera Utara. The test results using Partial Least Square (PLS) concluded that there was a direct effect on the quality of the website quality (webqual 4.0) on purchasing decisions, and there was no direct effect of e-service quality on purchasing decisions. There is no effect of website quality (webqual 4.0) on e-customer trust, and there is no effect of e-service quality on e-customer trust, on the e-customer trust variable there is a direct effect on purchasing decisions, then on indirect effects website quality (webqual 4.0) and e-service quality has no effect on purchasing decisions after being mediated by the e-customer trust variable.